Transoral Laser Microsurgery for Supraglottic Cancer - Ambrosch, Petra; Gonzalez-Donate, Mireia; Fazel, Asita; Schmalz, Claudia; Hedderich, Jürgen (Frontiers in Oncology, 2018)
Introduction Transoral laser microsurgery (TLM) is an accepted and effective treatment strategy for supraglottic carcinomas. Early supraglottic carcinoma has excellent outcomes independently of the treatment approach. The role of TLM for the treatment of locally advanced tumors is debated. Particularly, the functional outcomes after TLM have to be proven by functional assessment of large cohorts of patients. This study analyzes the oncologic and functional outcomes after TLM for supraglottic carcinomas. Patients and methods Ninety-one patients with pT1-pT4a supraglottic carcinomas treated between January 2002 and December 2012 were analyzed. Distribution of tumors (UICC 2010) was 11 patients with pT1, 31 patients with pT2, 36 patients with pT3, and 13 patients with pT4a tumors. Node status was positive in 40 (43.6%) patients; 61 (67.1%) patients had stage III or IVa disease. Local control and survival were estimated using the Kaplan–Meier method. For the assessment of functional outcomes, the MD Anderson Dysphagia Inventory (MDADI), the Voice Handicap Index-10 (VHI-10), and the performance status scale for head and neck cancer [Performance Status Scale for Head and Neck (PSS-HN)] were used. Results The median age was 62 years (range, 33–88 years). Fourteen (15.4%) patients developed a local or locoregional recurrence. The 5-year local control rate and 5-year ultimate local control rate were 72 and 92%, respectively. The 5-year overall survival rate was 63%. Twelve (13.2%) patients needed temporary tracheostomy. Sixty-eight (74.0%) patients had a nasogastric feeding tube post-operatively. At 1-year post-operative follow-up, only three patients were PEG dependent. The median VHI-10 score was 35, the median MDADI composite score was 80, and the median score of the domain “normalcy of diet” in the PSS-HN was 91. Conclusion The oncologic outcomes are comparable to the results of open surgery for early and advanced supraglottic carcinomas. Functional swallowing outcome is superior to open surgery and to concomitant chemoradiation. Patients treated with TLM perceive low levels of voice- and swallowing-related quality of life impairment.